Assessment of Acoustic Conditions in Worship Spaces Adjacent to Urban Noise : A Simulation Case Study of St. Thomas Garrison Church, Chennai - Beryl Raja, Divya Mahimairaj; Pradeepa, Chandramoul; Abdul Wafi, Razali; Nazli, Che Din (Faculty of Built Environment, University of Malaya, 2024)
According to its cultural and spiritual importance, church acoustics are intensively investigated. These architectural marvels serve religious worship, community events, and cultural preservation. Preserving these sites' historical importance and acoustic comfort requires understanding their complex sound transmission dynamics. However, urban noise severely reduces sacred sites acoustically. In view of their proximity to airports, highways, and Metro, this study explores the acoustics of Chennai's medieval St Thomas Garrison Church. Reverberation times (RT) at 500 and 1000 Hz exceed the optimum value, especially for speech purposes. Day and night background noises over 60 dBA affect speech transmission index (STI) and sound pressure level (SPL) distribution. These findings are also examined in relation to potential service interventions, such as amplification systems, in places of worship. This study suggests that urban planners, architects, and others can help preserve and improve religious experiences by addressing urban noise and improving church acoustics.